Research on Early Warning of Flash Flood Disaster Based on Multi-Source Rainfall Data Integration - LI Guanyi; YU Zexing (Renmin Zhujiang)
Flash flood is the main disaster that causes casualties in China,and it has the characteristics of abruptness,unpredictability,and harmfulness.In this study,the accumulated rainfall in the humid area of South China in different periods is calculated based on the integrated multi-source rainfall data,and the early warning of flash flood disasters is analyzed according to the dynamic rainfall early warning index analysis method.The method is applied to the small watershed of Maofeng Town in Nanxiong city and Bijia forest farm in Qingyuan city.The results show that compared with the actual time of flash flood disaster in the studied area,the warning is issued 3 h and 0.5 h in advance by the dynamic rainfall early warning index analysis method based on the multi-source rainfall data integration,which effectively prolongs the prediction period of flash flood disasters and gains more time for early warning release and personnel transfer.